DEVELOPMENT OF PROGRAM TO ENHANCE EXECUTIVE FUNCTION AND MOTOR COMPETENCY FOR UPPER ELEMENTARY SCHOOL STUDENTS - Pragobmas, Parichat; Tingsabhat, Suthana; Sarayuthpitak, Jintana (Academic Journal of Thailand National Sports University, 2023)
The purposes of this research were to: 1) develop executive function and motor competency program of upper elementary school students and 2) evaluate the effectiveness of executive function and motor competency program of upper elementary school students. The study samples consisted of 24 upper elementary school students. By means of simple random sampling, those samples were chosen from students in one school that voluntarily participated in the developed program and met the inclusion criteria. Data were analyzed by mean, standard deviation, and t-test. The results were as follows: 1) The developed program consisted of eight activities including (1) Pirates on the Treasure Island (2) The Conditions of the Big Bear (3) Blazing Flame (4) Giant Spider the Gatekeeper (5) White Rhino by the Stream (6) Fruit Jelly Wall (7) Red Circle Symbol and (8) Celebration Dance. This program was rated at the most suitable level. 2) At post-experiment period, it was found that the effectiveness of the developed program has resulted in a statistically significantly higher mean of executive function and motor competency of the students in the experiment group was significantly increased after the experiment at .05.